Post anesthesia ulcers in children: Two clinical cases. - Zini Carbone, Claudia Norma Haydee (2022)
The following article describes two clinical cases of post-anesthesia traumatic ulcers in children, after dental treatment, in which infiltration of local anesthesia was used as part of the therapeutic treatment for the loss of sensitivity of the sector to be treated. The effects of the anesthetic continued at the end of the treatment, which stimulated curiosity in children to suck or bite the soft tissue due to lack of sensitivity, this caused serious lesions in the oral mucosa. The importance of these post-anesthetic injuries lies in prevention, that is, the professional who attends pediatric patients, must prevent and avoid these serious injuries self-inflicted by the child, giving the recommendations verbally and in writing to the parents.